2004
DOI: 10.1111/j.1365-2249.2004.02587.x
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmunity gene expression portrait: specific signature that intersects or differentiates between multiple sclerosis and systemic lupus erythematosus

Abstract: SUMMARYAutoimmune diseases are either tissue-specific like multiple sclerosis (MS) or multisystemic like systemic lupus erythematosus (SLE), although clinically both exhibit common features. To gain insight into the properties of the genes involved in each disease we have investigated the gene expression signature of peripheral blood mononuclear cells (PBMC) in MS and SLE in comparison to healthy subjects. Total RNA was purified, hybridized to Genechip array and analysed in 36 subjects (13 relapsing-remitting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
73
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(80 citation statements)
references
References 38 publications
6
73
1
Order By: Relevance
“…Nevertheless, controversial differences between MS patients and healthy controls have been found in gene expression studies. Whereas earlier genetic studies showed HSPA1A overexpression in MS lesions (64,65,68), more recently HSPA1A expression was shown to be downregulated in the PBMC of MS patients (141)(142)(143). Histological studies in MS and EAE tissues have confirmed HSPA1A upregulation in CNS lesions; however, surprisingly, analysis of the baseline expression of Hsp70 genes in PBMC revealed no differences among MS patients, healthy controls or patients with rheumatoid arthritis.…”
Section: Hsp Genetic Studiesmentioning
confidence: 90%
“…Nevertheless, controversial differences between MS patients and healthy controls have been found in gene expression studies. Whereas earlier genetic studies showed HSPA1A overexpression in MS lesions (64,65,68), more recently HSPA1A expression was shown to be downregulated in the PBMC of MS patients (141)(142)(143). Histological studies in MS and EAE tissues have confirmed HSPA1A upregulation in CNS lesions; however, surprisingly, analysis of the baseline expression of Hsp70 genes in PBMC revealed no differences among MS patients, healthy controls or patients with rheumatoid arthritis.…”
Section: Hsp Genetic Studiesmentioning
confidence: 90%
“…Recently, microarray analysis in the case of sev-eral autoimmune diseases (SLE, rheumatoid arthritis, multiple sclerosis, and type I diabetes) was found to yield a common expression signature (17,40). The genes that we identified might be unique to SLE, or they might be genes with potential relevance for other autoimmune diseases as well.…”
Section: Elmann Et Almentioning
confidence: 86%
“…Rus et al (15) showed, for example, that transcripts of Tnfsf10 (encoding TRAIL) as well as transcripts of Tnfsf10C and Tnfsf10D (both encoding TRAIL receptors) were increased in PBMCs from lupus patients relative to controls. Also, Tnfsf9 was one of the genes shown to differentiate PBMCs of SLE patients from those of healthy controls (40).…”
Section: Elmann Et Almentioning
confidence: 99%
“…Gene profiling experiments have allowed the identification of novel and unsuspected pathways involved in disease etiology, including in rheumatic and immune diseases [4][5][6]. Pathway analysis of differentially expressed genes is a useful approach to highlight undetected patterns in the data and to determine which differentially expressed genes to follow-up in independent assays such as association studies.…”
Section: Introductionmentioning
confidence: 99%